Catoptric Anamorphosis on Free-Form Reflective Surfaces (diségno, 2020)
The study focuses on the definition of a geometric methodology for the use of catoptric anamorphosis in contemporary architecture. The particular projective phenomenon is illustrated, showing typological-geometric properties, responding to mechanisms of light reflection. It is pointed out that previous experience, over the centuries, employed the technique, relegating its realisation exclusively to reflecting devices realised by simple geometries, on a small scale and almost exclusively for convex mirrors. Wanting to extend the use of the projective phenomenon and experiment with the expressive potential on reflective surfaces of a complex geometric free-form nature, traditional geometric methods limit the design and prior control of the results, thus causing the desired effect to fail. Therefore, a generalisable methodological process of implementation is proposed, defined through the use of algorithmic-parametric procedures, for the determination of deformed images, describing possible subsequent developments.
Keywords: anamorphosis; science of representation; generative algorithm; free-form; design